BIOSORPSI Cr(III) PADA BIOSORBEN SERAT SABUT KELAPA HIJAU TERAMOBILISASI EDTA - I Wayan Sudiarta; Wahyu Dwijani Sulihingtyas (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Studies on biosorption of Cr(III) on coconut fiber immobilized with EDTA biosorbent (B-EDTA) have been conducted. These studies included the optimization of EDTA immobilization on biosorbent, optimization of Cr(III) biosorption on B-EDTA biosorbent that include pH dan contact time biosorption, and also studied the mechanisms of Cr(III) interactions on biosorbent B-EDTA by squential desorption.The result showed that the optimum EDTA immobilization on biosorbent E-EDTA occured at ratio of 1mmol EDTA : 4g biosorbet (0,25mmol/g ), with the surface acidity of biosorbent B-EDTA of 2,18 mmol/g. Optimum biosorption process of Cr(III) on biosorbent B-EDTA occured at pH = 3, contact time of 120 minutes, with the biosorption capacity of Cr(III) on biosorbent B-EDTA of 8,32 mg/g. The squential desorption studies show that the interaction of Cr(III) on biosorbent B-EDTA occured predominantly through physical adsorption namely Van der Waals bonding.